Double-differential cross sections and kerma coefficients for light-charged particles produced by 96 MeV neutrons on carbon - Tippawan U. (2017)
Double-differential cross sections of inclusive light-ion (p, d, t, 3 He and α) production in carbon induced by 96 MeV neutrons have been measured at eight laboratory angles from 20° to 160° in steps of 20°. Experimental techniques, as well as procedures for data taking and data reduction, are presented. Deduced energy-differential and production cross sections are herewith reported. Experimental cross sections are compared with theoretical reaction model calculations and experimental data in the literature. The measured production cross sections for protons, deuterons, tritons, 3 He, and α particles support the trends suggested by data at lower energies. Deduced partial kerma coefficients for carbon are also shown. © 2010 Published by Elsevier Ltd. All rights reserved.